Chondrosarcoma of trachea: case report of successful surgical treatment of local recurrence - Z. A.-G. Radzhabova; M. A. Kotov; A. S. Mitrophanov; O. I. Ponomareva; M. A. Radzhabova; E. V. Levchenko (Опухоли головы и шеи, 2019)
The study objective is to report a case of tracheal chondrosarcoma, which is a very rare malignant tumor. Only 18 cases have been described so far in English medical literature.Materials and methods. A 74-year-old male patient visited an otorhinolaryngologist in August 2011 with complaints of hoarseness of voice, which have been gradually increasing during the last 3 years. The patient was diagnosed with myxoid chondrosarcoma.Results. In September 2011, the patient underwent thyroidectomy and circular resection of the trachea at the level of its second ring with the creation of a tracheal anastomosis. This volume of surgery was determined by the presence a thyroid nodule in the right thyroid lobe, which invaded the cricoid cartilage and the first ring of the trachea. In November-December 2011, the patient underwent a course of adjuvant external beam radiotherapy with a total dose of 50 Gy delivered in 2.0 Gy fractions, 5 days per week. No cancer recurrence had been observed during 3 years and 9 months of follow up. In September 2015, the patients was found to have a 24-mm thyroid nodule with an exophytic component in the right thyroid cartilage plate. This finding was considered as recurrent chondrosarcoma. In May 2016, the patient had laryngectomy. We performed margin-negative (R0) resection. The patient has now been in remission for 2 years and 9 months.Conclusion. We demonstrate successful treatment of a patient with tracheal chondrosarcoma with a long-term remission after surgery for recurrent tumor.